On the coefficients of the expansion of elements from C[0, 1] space by the Faber-Schauder system - M. G. Grigoryan; A. A. Sargsyan (Journal of Function Spaces and Applications)
Elements (functions) of continuous on [0, 1] functions space (C[0, 1]) are described which have 1/2-monotone coefficients of the expansion by the Faber-Schauder system.